YIRIK SHOXLI QORAMOLLARNI DEMODEX BOVIS КАNАLARI BILAN ZARARLANISHI BO’YICHA TADQIQOT USLUBLAR VA MATERIAL TO’PLASH - Bobonazarov , Gappar; Jo’rayeva , Iroda; Abdullayev , O’lmas (Actual problems and prospects of the study of the fauna, 2024)
This article provides information on research methods, material collection, and diagnosis of animal demodicosis to determine the infestation of large horned cattle with the Demodex bovis mite.